O uso de expressões referenciais nominais em produções de texto opinativo no Ensino Fundamental - Bertollo, Daniele (2020)
The aim of this paper is to investigate in year 9 students’ essays if there were development in the use of referencial direct expressions from the referencial theory. We study the relation between linguistic theories that approach the process of referencing and its application in the teaching of native languages, more specifically in what concerns the work with the textual production axis. We take to analysis eight texts produced by four students, being four texts correspondent to Production 1 (initial generation) and four texts to Production 2 (produced by the same students, after the work with the theme in the classroom). We promoted comparative analysis between the two productions of each student’s text to observe if there are advancements in the construction of the referential chain, considering the context of interlocution and the anaphoric resumption processes. This research is qualitative and follows the interpretivist bias. It supports itself in bibliographical revision and is centered in methods and procedures that aim to describe and interpret the phenomenon that is established in the texts, following theoretical orientations from the field of Textual Linguistics, especially in what concerns the interactionist socio-cognitive perspective. We take as basis to our analysis studies presented by Mondada and Dubois (2017), Lyons (1977), Koch (2001, 2002, 2003, 2005a, 2008, 2011), Koch and Elias (2017, 2018), Cavalcante, Custódio Filho e Brito (2014) and Roncarati (2010), among others that make up the referencing studies scene. As a result, we observed in the texts under analysis the strategic use of the following procedures of resumption: core name change, core name reiteration with recategorization and core name reiteration without recategorization. By comparing the two texts from each student, we verified an increase of points from the referent in question and more informative or evaluative recategorizations, strategies that contributed to approximate the text to the objectives of the proposed interaction.